A note on Indian hare Lepus nigricollis: presence beyond the IUCN distribution in the Himalayas - Avantika Thapa; Aditya Pradhan; Paromit Chatterjee; Ashutosh Singh (Academia Biology)
Indian hare Lepus nigricollis have a vast distribution in southern Asia with several subspecies. Even though it is distributed in a large area, the species lacks regional assessment and has been understudied for taxonomy, ecology, and demography. The species is stated to be absent from the high reaches of the Himalayas; however, several records reveal the presence of the species in the higher reaches of the Himalayas. In this article, we present records of Indian hare from the higher reaches of the Himalayas based on questionnaire survey, literature review, and directed sightings, which could be used to reassign its distribution range.